Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1038/s41598-018-34929-z
|View full text |Cite
|
Sign up to set email alerts
|

El Niño drives a widespread ulcerative skin disease outbreak in Galapagos marine fishes

Abstract: Climate change increases local climatic variation and unpredictability, which can alter ecological interactions and trigger wildlife disease outbreaks. Here we describe an unprecedented multi-species outbreak of wild fish disease driven by a climate perturbation. The 2015–16 El Niño generated a +2.5 °C sea surface temperature anomaly in the Galapagos Islands lasting six months. This coincided with a novel ulcerative skin disease affecting 18 teleost species from 13 different families. Disease signs included sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…The present PCA results (Figure ) strongly suggest that interannual variations in local environmental factors (i.e., temperature, salinity, climate season, and ENSO index) had a substantial effect on parasite infracommunity structure. For example, infracommunity parameter values were significantly lower in the 2015 sampling (Table ), during one of the strongest recent ENSO events in the Pacific region, which generated an abnormally high temperature increase of up to +2.5°C in some regions of the tropical Pacific (Lamb et al, ). During this climate event, surface temperature (30.2°C) and salinity (35.5 ppt) in Acapulco Bay were significantly higher than in other sampling years (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The present PCA results (Figure ) strongly suggest that interannual variations in local environmental factors (i.e., temperature, salinity, climate season, and ENSO index) had a substantial effect on parasite infracommunity structure. For example, infracommunity parameter values were significantly lower in the 2015 sampling (Table ), during one of the strongest recent ENSO events in the Pacific region, which generated an abnormally high temperature increase of up to +2.5°C in some regions of the tropical Pacific (Lamb et al, ). During this climate event, surface temperature (30.2°C) and salinity (35.5 ppt) in Acapulco Bay were significantly higher than in other sampling years (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…During this climate event, surface temperature (30.2°C) and salinity (35.5 ppt) in Acapulco Bay were significantly higher than in other sampling years (Table ). Abnormal increases in sea surface temperature can decrease the productivity of food webs, affecting the parasite transmission processes of many trophically transmitted parasites due to population decreases in potential intermediate or final hosts (Lamb et al, ; Jacobson et al, ; Oliva et al, ). In Acapulco Bay slight changes in the temperature and salinity parameters can be enough to generate notable changes in copepod community species composition throughout the year (Rojas‐Herrera, Violante‐Gonzalez, Garcia‐Ibañez, Villerias‐Salinas, & Moreno‐Diaz, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that climate change strongly affects performance, population dynamics and distribution of marine organisms [6,17,18,19]. In particular, ENSO affects host-pathogen relationships of some marine organisms by reducing host immunity and increasing pathogen virulence [8,16,19,20,21,22]. However, most of these studies have been carried out on fungal, viral, protozoan [8,22,23,24,25] or internal metazoan parasites [9,26,27], while ectoparasites, which are more exposed and influenced by environmental variables, remain poorly studied.…”
Section: Introductionmentioning
confidence: 99%